Pengaruh Authentic Leadership terhadap Organizational Commitment yang Dimediasi oleh Knowledge Sharing - Perkasa, I Gede Tito Dana; Rahyuda, Agoes Ganesha; Dewi, I Gusti Ayu Manuati; Surya, Ida Bagus Ketut (Jurnal Bisnis Indonesia, 2024)
Organizational commitment is the nature of the relationship between an individual and the workorganization, where the individual has confidence in the values and goals of the work organization,there is a willingness to use his efforts seriously for the benefit of the organization. Based on theexplanation regarding the existence of an organizational commitment phenomenon in the companyPT. Pak Oles Tokcer's work is influenced by the lack of emphasis on authentic leadership andknowledge sharing, so it is necessary to conduct research to explain how the knowledge sharingrelationship mediates the influence of authentic leadership on organizational commitment. Thisresearch is causal associative research using a quantitative approach. This research was conducted atPT. The work of Pak Oles Tokcer, located at Jl. Nusa Kambangan, No. 7X, Dauh Puri, West DenpasarDistrict, Denpasar City, Bali. The population in this study were all employees of PT. Pak OlesTokcer's work is located in Bali Province with 117 employees. The sampling technique used in thisresearch is saturated sampling which is included in non-probability sampling. The data analysistechnique in this research uses two analysis techniques, namely descriptive statistical analysis andinferential statistical analysis using Structural Equation Modeling (SEM). The aim of this research isto analyze the influence of Authentic Leadership on Organizational Commitment mediated byKnowledge Sharing.Keywords: Social Identity Theory; Organizational Commitment; Knowledge Sharing; AuthenticLeadership